2022
DOI: 10.1038/s41427-022-00380-w
|View full text |Cite
|
Sign up to set email alerts
|

Possible permanent Dirac- to Weyl-semimetal phase transition by ion implantation

Abstract: Three-dimensional (3D) topological semimetals (TSMs) are a new class of Dirac materials that can be viewed as 3D graphene and are referred to as Dirac semimetals (DSMs) or Weyl semimetals (WSMs) depending on whether time reversal symmetry and/or inversion symmetry are protected, respectively. Despite some interesting results on Dirac- to Weyl-semimetal phase transitions under conditions of low temperature or strong magnetic field (B), all of them are reversible phenomena. Here, we report for the first time a p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
4

Relationship

2
2

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 45 publications
0
3
1
Order By: Relevance
“…This might be explained by the heating of the sample due to too large laser power used in their experiments. It is more difficult to explain why Lee et al found a slightly larger frequency of the E g mode and a slightly smaller frequency of the A 1g mode in the case of a single-crystalline sample with x = 0.04 [60] than for our x = 0.05 sample.…”
Section: Raman Scatteringcontrasting
confidence: 67%
See 1 more Smart Citation
“…This might be explained by the heating of the sample due to too large laser power used in their experiments. It is more difficult to explain why Lee et al found a slightly larger frequency of the E g mode and a slightly smaller frequency of the A 1g mode in the case of a single-crystalline sample with x = 0.04 [60] than for our x = 0.05 sample.…”
Section: Raman Scatteringcontrasting
confidence: 67%
“…Thus, in addition to the two lowest energy modes close to those of Bi due to Bi-Bi vibrations, and the two modes at about 114 cm −1 and 140-150 cm −1 due to Sb-Sb vibrations, Lannin attributed the fifth peak at about 120 cm −1 to Bi-Sb vibrations with A 1g symmetry, i.e., to local mode vibration of Sb atoms surrounded by Bi atoms as first neighbors [55]. In the more recent works, Sultana et al also observed only additional peaks at about 120 cm −1 and 140 cm −1 [55], whereas Zhao et al observed only these peaks for x ≤ 0.18 and all the five peaks only for x ≥ 0.27 [56], and Lee et al observed only one weak additional peak at about 118 cm −1 in their sample with x =0.04 [60]. In contrast, in our samples, we observed the peak at around 110 cm −1 even for low Sb content, and it is located at lower frequencies than in single-crystalline samples [54,55] and the same frequency as in the 2D layer of Bi 0.65 Sb 0.35 studied by Zhao et al [58].…”
Section: Raman Scatteringmentioning
confidence: 90%
“…NMR is known to result from various mechanisms, including chiral anomaly, which are discriminated by its field and temperature dependence. [ 31 ] Stronger NMR at higher T seems to be related to a crossover behavior of WAL to WL at higher T based on the disappearance of the cusp at higher T, as discussed previously. [ 11 ] In particular, the WAL is very strong at low T, as shown in Figure 1 (and Figure S3, Supporting Information), thereby making the NMR invisible, but it becomes visible as the WAL disappears at high T. Figure 1c,d shows the MR behaviors of 2 nm film in both configurations (for 3‐ and 4‐nm Bi 0.96 Sb 0.04 films, see Figure S3, Supporting Information).…”
Section: Resultsmentioning
confidence: 56%
“…Although dissipationless channels have already been observed at the natural edges of TI crystals 20 , a missing step is a precise top-down method to spatially engineer nanoscale arrays of conducting channels for scalable integrated circuitry, which would require regions of both ℤ 2s = 1 and ℤ 2s = 0. Adopting the surface engineering paradigm from silicon technology, an effective way to do this would be to define the channels using lithography of monolithic crystal surfaces enabled by ion beams [21][22][23] . So far there has been no demonstration of this technique, which is well-known in other microelectronics, to pattern the position of topological edge states.…”
mentioning
confidence: 99%